Asuhan Kebidanan Continuity of Care Ny. N Umur 29 Tahun di Puskesmas Kajen I Kabupaten Pekalongan - Wiwit Puspita Dewi; Luvi Dian Afriani (Universitas Ngudi Waluyo, 2025)
Continuity of care is the provision of obstetric care from pregnancy, childbirth, puerperium, neonates to decide to use birth control. This is intended as an effort to help monitor and detect possible possibilities The onset of complications that accompany the mother and baby from the time of pregnancy until the mother uses birth control. Midwifery care methods at Kajen I Community Health Center, Pekalongan Regency and through home visits by providing counseling according to the needs of mothers. The obstetric care given to Mrs.